Polityka dystrybucji przedsiębiorstwa jako element konkurencyjności w agrobiznesie - Grzybowska-Brzezińska, Mariola (Politics of Distribution of Enterprise as An Element of Competitiveness in Agribusiness, 2006)
This project contains information on distribution as an element of "mix" marketing of our grocery products distribution with an emphasis on dairy products.In the present market situation it is difficult to get competitive advantage for a product. It leads to a situation in which companies need to pay more attention to a better distribution system.The main assumption of distribution is providing a product to a customer in an appropriate form, place and time.The company uses four channels of distribution: warehouse receivers, supermarkets, retailers and direct receivers.The survey on sale, structure and dynamics of changes shows that receivers have the main impact on the mentioned markets. The markets are defined as: local, regional and domestic. In retail sale there is a tendency of shortening the channels of distributor considering the height cost of service on the other market. Due to that process there is a concentration on the regional market (70% sale in this channel).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 288-294